Linguistic perspectives on second language acquisition - Gass, Susan M.; Schachter, Jacquelyn (Cambridge [England]: New York : Cambridge University Press, 1990)
The author shows how similarities and differences between languages can influence grammar, vocabulary, and pronunciation acquisition.
Includes index.
Keywords: Second language acquisition; Applied linguistics; Language acquisition